A comparison of self and proxy quality of life ratings for people with dementia and their carers: a European prospective cohort study. (2nd January 2020) - O'Shea, E.; Hopper, L.; Marques, M.; Gonçalves-Pereira, M.; Woods, B.; Jelley, H.; Verhey, F.; Kerpershoek, L.; Wolfs, C.; de Vugt, M.; Stephan, A.; Bieber, A.; et al.
Abstract: Objectives: To identify correlates of self-rated and proxy-rated quality of life (QoL) in people with dementia on (i) a dementia-specific and (ii) a capability-wellbeing QoL measure at baseline and 12-month follow-up, and to consider such factors in the context of QoL intervention development. Method: Prospective clinical and demographic data were collected from 451 community-dwelling dyads (mild-moderate dementia) across eight European countries. QoL was measured using the QOL-AD and the ICECAP-O. Multivariate modelling identified correlates of self- and proxy-rated QoL at baseline and at 12-month follow-up. Results: Carer's proxy-ratings of QoL were significantly lower than self-ratings at all time-points for both measures. Proxy-ratings declined over time, but self-ratings remained stable. Baseline predictors of greater self-rated QoL were education, and greater functional ability and relationship quality. Greater proxy-rated QoL was associated with education and greater functional ability, relationship quality, carer social support and carer QoL, lower carer anxiety/depression and less severe neuropsychiatric symptoms in people with dementia. At follow-up, greater self-rated QoL was predicted by greater functional ability, relationship quality, carer social support and having a spousal carer. Greater proxy-rated QoL at follow-up was associated with the same factors as at baseline; however, the dyad living together was an additional predictive factor. Conclusion: Both proxy-ratings and self-ratings of QoL should be interpreted with caution and in the context of each individual caregiving relationship. Different functional, psychosocial, relational and contextual factors influence self- and proxy-ratings, and both sets of factors should be considered in the context of QoL intervention development for the dyad.